2016
DOI: 10.1055/s-0036-1597273
|View full text |Cite
|
Sign up to set email alerts
|

Identifying an Ideal Time Frame for Staged Bilateral Total Knee Arthroplasty to Maximize Functional Outcome

Abstract: Compared with staged bilateral total knee arthroplasty (TKA), simultaneous bilateral TKA carries a higher risk of cardiac complications, pulmonary complications, and mortality, especially in patients with preexisting cardiopulmonary disease or advanced age. However, the period of time between staged TKAs that would eliminate these increased risks has yet to be determined. The purpose of this study is to evaluate complication rates and functional outcome in patients who underwent staged bilateral TKA and to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Another study of 306 patients with one to 12 months between procedures found no association between surgical interval and any outcomes (complications, 90-day readmission, and OKS at two years postoperatively). 37 This study is not without limitations. Because the first TKA is assumed to be undertaken on the worst knee, the first and second TKAs are not directly comparable although our within-subject design accounts for other potential confounders.…”
Section: Discussionmentioning
confidence: 89%
“…Another study of 306 patients with one to 12 months between procedures found no association between surgical interval and any outcomes (complications, 90-day readmission, and OKS at two years postoperatively). 37 This study is not without limitations. Because the first TKA is assumed to be undertaken on the worst knee, the first and second TKAs are not directly comparable although our within-subject design accounts for other potential confounders.…”
Section: Discussionmentioning
confidence: 89%
“…Yeh et al . revealed no significant differences in complication rates and knee functional outcomes evaluated by the Oxford Knee Score and Short‐Form‐36 among intervals of 31–90, 91–180, 181–270, and 271–365 days 21 . Chen et al .…”
Section: Discussionmentioning
confidence: 96%
“…revealed no significant differences in complication rates and knee functional outcomes evaluated by the Oxford Knee Score and Short‐Form‐36 among intervals of 31–90, 91–180, 181–270, and 271–365 days. 21 Chen et al . found no difference between staged groups (21–90, 91–180, 181–270, and 271–360 days after the first TKA).…”
Section: Discussionmentioning
confidence: 99%
“…Although the optimal timing for staged BTKA remains inconclusive, there is some agreement that an interval of at least 3 months between the first and second TKA is necessary for minimizing postoperative complications and facilitating the recovery process 38,91,100,101 . Another common timing interval is 6 weeks between operations.…”
Section: Other Considerationsmentioning
confidence: 99%